The Hybrid Delay: A New Approach for Nipple-sparing Mastectomy in Macromastia - Jay Arthur Jensen, MD, FACS; Armando E. Giuliano, MD, FACS, FRCS(Ed) (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. Patients with macromastia or breast ptosis can undergo a nipple-sparing mastectomy if their mastectomy flaps are delayed or if they are subjected to a breast reduction procedure and later undergo mastectomy. Methods:. In this report, we describe a new technique to combine these two approaches by initially performing a subtotal mastectomy through a Wise keyhole incision in combination with the retention of the nipple -areolar complex on an inferior pedicle flap. A tissue expander and an allograft are routinely placed during this first stage. At a second stage, the inferior pedicle tissue is removed and submitted for pathological examination at the same time as the tissue expander is removed and replaced with a silicone or saline implant or autologous flap. Results:. The Hybrid Delay procedure has been performed on three women (six breasts). Nipples were preserved in all patients. Final pathology did not reveal any cancer in the inferior pedicle preserved during the first procedure but removed and tested following the second. Conclusion:. By allowing the nipple to be safely transferred using the inferior pedicle flap, and then removing the inferior pedicle tissue during the subsequent reconstructive stage, women with macromastia and breast ptosis can be offered nipple-sparing mastectomy in the usual 2-stage reconstructive timing.